Marking otoliths of brown trout (Salmo trutta L.) embryos with alizarin red S. (7th December 2012) - Unfer, G.; Pinter, K.
Summary In this study a time‐ and cost effective method for marking early life stages of brown trout (Salmo trutta L.) with alizarin red S (ARS) is presented. The main intention was the development of a protocol to mark embryos. When stocking eyed‐eggs, later recognition depends on an adequate tagging method featuring reasonable expenditures, low mortality and high marking success. Best results were obtained using ARS concentrations of 500 mg/l. Consistently clearly visible marks could be detected under a fluorescence‐stereomicroscope equipped with a dsRed filter, without processing the otoliths.